Coupling of the Quasi‐Biweekly Oscillation of the Tibetan Plateau Summer Monsoon With the Arctic Oscillation. Issue 15 (30th April 2018) - Wang, Meirong; Wang, Jun; Duan, Anmin; Liu, Yimin; Zhou, Shunwu
Abstract: The intraseasonal variation of the Tibetan Plateau summer monsoon (TPSM) during 1979–2011 is investigated. The TPSM shows a dominant quasi‐biweekly oscillation (QBWO) in most summer seasons, and its active/break phases are closely related to more/less precipitation over the Tibetan Plateau. We suggest that the TPSM QBWO is associated with a southeastward propagating nonstationary wave train in the middle and upper troposphere. It shows equivalent barotropic vertical structures over the midlatitudes and a baroclinic structure over the eastern Tibetan Plateau. Wave activity flux analysis indicates that it originates from northern Europe, which is an active center of the summertime Arctic Oscillation (AO). The AO also shows significant QBWO signals and leads TPSM QBWO by about 13 days. Phase composite and wave activity flux analyses of AO QBWO confirmed that the wave train influences TPSM QBWO, suggesting that AO plays an important role in the TPSM on a 10‐ to 20‐day timescale. Plain Language Summary: The intraseasonal variation of the Tibetan Plateau summer monsoon (TPSM) during 1979–2011 is investigated. We suggest that TPSM shows a dominant quasi‐biweekly oscillation (QBWO) in most summer seasons and it is associated with a southeastward propagating nonstationary wave train in the middle and upper troposphere. Wave activity flux analysis indicates that the wave train originates from northern Europe, which is an active center of the summertime Arctic Oscillation (AO). The AO also shows significant QBWO signals and leads TPSM QBWO by about 13 days. Phase composite and wave activity flux analyses of AO QBWO confirmed that the wave train influences TPSM QBWO, suggesting that AO plays an important role in the TPSM on a 10‐ to 20‐day timescale. It is more complicated to understand wave activities of the midlatitudes than along the equator, and at present the related studies are limited. The results of this paper are important to understand the weather and climate of Tibetan Plateau and its linkages to the wave train in the midlatitudes associated with the summer AO. This article provides a basic reference for the study on the intraseasonal oscillation over the midlatitudes and Tibetan Plateau area. Key Points: The Tibetan Plateau summer monsoon (TPSM) has a dominant quasi‐biweekly oscillation (QBWO) in most summer seasons The TPSM QBWO is associated with a southeastward propagating nonstationary wave train originating from northern Europe Northern Europe is an active center of the summertime Arctic Oscillation, and the Arctic Oscillation wave train contributes to the TPSM QBWO